Translating Hélène Cixous: French Feminism(s) and Anglo-American Feminist Theory - Penrod, Lynn (TTR, 1993)
AbstractTranslating Hélène Cixous: French Feminism(s) and Anglo-American Feminist Theory — The works of H. Cixous in English translation represent an interesting case study to examine the relevant choice factors which enter into the project of translation. Cixous, as a representative of what the Anglo-American feminist community has described as "French Feminism" remains best known for two works, both written nearly twenty years ago, "Le Rire de la Méduse" (1975) and La Jeune Née (1976). Although the former text was translated almost immediately, the latter waited a decade before reaching an English reading audience. Compared to Luce Irigaray and Julia Kristeva, Cixous remains the least available in translation to an English audience despite a prolific output over the course of her career. The politics of choice, the décalage factor, the problems of academic translators and the "difficulty factor" are discussed as they relate to Cixous's translated works.